Simulation of emulsion evolution in shear flow field under the control of bidirectional pulsed electric field - Heping Wang; Yi Wu; Yijian Peng; Xiaohang Zhang (PLoS ONE, 2026)
Electrostatic demulsification is a widely used technique for treating high-water-cut emulsions (O/W type). However, in high-water-cut emulsions, continuous electric fields often lead to short-circuiting and chain formation. Meanwhile, pure shear fields rely on random collisions, which is inefficient for fine droplets. To address these limitations, this article established a lattice Boltzmann model coupled with electric and shear field. It explored the impact of the combined action of bidirectional pulsed electric field (BPEF) and shear field on the demulsification process. Simulation results reveal that: Under the action of pure shear field, increasing the shear effect will lead oil droplets to move around the flow field center, and forming a stable state eventually. However, after applying bidirectional pulsed electric field on both sides of the flow field, the electric field force breaks this stable state and promotes further aggregation of oil droplets. Analysis of streamline diagrams indicates that: Bidirectional pulsed electric field periodically changes the direction of the electric field force. It leads to induce an unbalanced velocity distribution in the flow field. And this phenomenon can accelerate or decelerate the aggregation of oil droplets. Quantitative analysis indicates that the synergistic coupling of BPEF and shear field significantly outperforms single-field methods. Under the optimal electric potential of V = 300 and shear rate of γ = 0.001 , the composite morpho-dynamic index ( D r ) reached 11.5. This represents a 4.7-fold increase compared to the pure shear field ( D r ≈ 2.0 ) and a 109% improvement compared to the low-voltage condition (V = 100), indicating a highly aggregated and moderately deformed stable state. These simulation results are significant important for understand the synergistic demulsification effects of electric and shear fields.